The Palestinian Issue in the Media Discourses of Terrorist Organizations - Salama, Adel (Politikologija religije, 2023)
This article examines the extent to which the Palestinian issue is exploited to promote cross-border terrorist movements. The analytical descriptive approach is employed to explore the evolution of the terrorist organizations, and trace the ideology, means, and content of their media discourse. The article reveals that the extremist groups utilized the value, sanctity, and nobility of the Palestinian issue to influence Arab and Islamic societies in an attempt to give legitimacy and credibility to their presence, media discourse, and terrorist acts; disseminate their extremist ideologies; rally support and recruit new elements, and emotionally influence the public perception. The article also concluded that these terrorist organizations refrained from targeting the Israeli occupation and opposed the Palestinian national narrative about the national and political nature of the Palestinian struggle.